Selection of TikTok Content Based on User Engagement Criteria Using the Analytic Hierarchy Process - Citra Wiguna; Sri Mulyana; Retantyo Wardoyo (JUITA: Jurnal Informatika, 2023)
Indonesia has 106.9 million active TikTok users aged 18 and above. TikTok is designed for engagement in many ways, as it actively encourages two-way communication and eye-catching content. Uploaded content must have its uniqueness variable. In increasing the engagement of a TikTok account, criteria are chosen based on the COBRA concept (consuming, contributing, and creating) and alternatives based on social media content trends in Indonesia (tutorial, educational, a day in my life, behind the scene dan tips and trick). This research was conducted by implementing the Analytic Hierarchy Process (AHP) method to select the content that must be prioritized to get engagement from the wider community. From the data processing results obtained, tutorial content is the best content in increasing engagement results, especially TikTok. Content that has the lowest engagement is behind the scene content. Further research can be carried out through a group decision support system with various related experts. It can also be combined with the BORDA, TOPSIS, and Profile Matching methods to optimize ranking results.